An empirical study on the modification of China's current urban social security system. Issue 2 (2nd April 2016) - Huang, Guan; Chen, Yufeng; Liu, Mengque; Wu, Jianzhen
ABSTRACT: This study challenges the conventional correlation between economic performance and the level of the development of social security systems. By focusing on China's urban areas, we provide an overview of the components and benefits, from a comparative perspective, of China's current social security system. We also create a comprehensive and generally applicable method using factors such as economics and population, among others, as standards to evaluate the efficacy of China's system. In order to demonstrate our primary hypothesis – that the Chinese Communist Party government has to modify its social security system to adapt to or bring about changes in the basis of its legitimacy – we analyse Chinese social security records and other related data after 1949 by statistical methods. The formula we provide in this study can be used to forecast China's expenditure on its urban social security system, and other scholars can apply our methods to countries in which conditions are broadly similar.